2018
DOI: 10.1016/j.dadm.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A novel detection method of cleaved plasma high‐molecular‐weight kininogen reveals its correlation with Alzheimer's pathology and cognitive impairment

Abstract: Introduction Accumulation of β-amyloid is a pathological hallmark of Alzheimer's disease (AD). β-Amyloid activates the plasma contact system leading to kallikrein-mediated cleavage of intact high-molecular-weight kininogen (HKi) to cleaved high-molecular-weight kininogen (HKc). Increased HKi cleavage is observed in plasma of AD patients and mouse models by Western blot. For potential diagnostic purposes, a more quantitative method that can measure HKc levels in plasma with high sensitivity and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 41 publications
1
54
0
Order By: Relevance
“…65,[67][68][69][70][71]73 While there have been technological challenges to developing these tests, recent studies demonstrated promising results and suggest that they will be available for routine clinical use in the future, possibly in combination with each other or some of the other biomarkers in development. [57][58][59][60][61][62] Our calculations underscore that a combination of cognitive testing and plasma biomarkers is probably necessary for efficient testing for MCI due to AD in primary care settings. Both the MMSE and the MoCA when used alone would result in 4 to 5 false positives for every 1 true-positive case.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…65,[67][68][69][70][71]73 While there have been technological challenges to developing these tests, recent studies demonstrated promising results and suggest that they will be available for routine clinical use in the future, possibly in combination with each other or some of the other biomarkers in development. [57][58][59][60][61][62] Our calculations underscore that a combination of cognitive testing and plasma biomarkers is probably necessary for efficient testing for MCI due to AD in primary care settings. Both the MMSE and the MoCA when used alone would result in 4 to 5 false positives for every 1 true-positive case.…”
Section: Discussionmentioning
confidence: 83%
“…Several plasma biomarkers that are specific to the AD pathology, such as A␤ and tau, or indicative of nonspecific neuronal injury, such as neurofilament light chain are in development, and others are being explored. [57][58][59][60][61][62] Similar to CSF biomarkers, 8 plasma biomarkers may be most useful when used in combination.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Therefore, we determined levels of cHK in the plasma samples of sickle patients and healthy controls by ELISA as previously described. 29 We found that the levels of cHK were significantly increased in sickle cell patient samples ( Figure 1A), whereas levels of total intact HK (iHK) were not different between the two groups ( Figure 1B). Moreover, the ratio of cHK/iHK was also elevated in SCD patient plasma ( Figure 1C).…”
Section: Re Sults 31 | Cleavage Of Kininogen Is Increased In Sicklmentioning
confidence: 88%
“…15 A recently developed detection method of cleaved plasma KNG1 has been tested and further supported the theory that decreased levels of intact KNG1 and increased levels of cleaved KNG1 in AD plasma are associated with dementia and neuritic plaque scores, and may be used as novel AD markers. 16 Finally, an antibody against highmolecular-weight kininogen has been developed and shown to block beta-amyloid-induced bradykinin release in human plasma, suggesting new treatment strategies against bradykinin-driven pathologies. 17 In our study, higher CSF levels of KNG1 (not distinguishing between intact and cleaved) were found in patients with low RBANS score.…”
Section: Discussionmentioning
confidence: 99%